Biomassa dan Karbon Tersimpan Diatas Tanah Pada Hutan Rakyat Agroforestri Di Kecamatan Bulo Kabupaten Polman. - Irundu, Daud; Andi Irmayanti Idris; Prayogi Sudiatmoko; Irlan (Jurnal Hutan dan Masyarakat, 2023)
Global warming has a huge negative impact on all living things, both humans, animals and plants. The cause of global warming is due to an increase in the concentration of carbon dioxide (CO2). Agroforestry pattern community forests have a good role in efforts to reduce gas emissions in the atmosphere. Vegetation found in community forests can absorb carbon through photosynthesis and release carbon through respiration, in the process of photosynthesis vegetation produces O2 and energy and some is stored in the form of biomass. This study aims to determine the potential of biomass and carbon stored in agroforestry-patterned community forests in Polewali Mandar District, West Sulawesi. Data collection was carried out in 9 villages in Bulo District with a total of 27 plots measuring 20 x 20 m. The data collected included tree diameter, tree height and tree species. data analysis using allometric equations according to tree species to obtain biomass values. while for the stored carbon value obtained from biomass products of 0.47. The results showed that the plant that dominated the highest value of biomass and carbon was durian. The total biomass in the community forest with the agroforestry pattern in Polewali Mandar Regency is 90.62 ton/ha while the total value of stored carbon is 42.59 ton/ha.